Sustainability of selected private schools in Rizal - Lindo, Eloida Fernandez (2006)
The study looked into the external and internal factors affecting the sustainability of private schools in Rizal and the leadership styles of principals in maintaining internal integration. Stakeholders, principals, school owners, and Board of Trustees from ten private basic education schools operating for more than 20 years served as the sample of the study. Data were gathered through survey and interviews. Teachers, students, and parents believe that internal integration factors affect growth, survival, and sustainability of private schools in Rizal. The modified integrated leadership style of Filipino principals helps balance the internal integration factors and external factors that affect the sustainability of the school. Financial and human resource management are also significant factors for school sustainability.
Thesis (M.A. Educational Administration)--University of the Philippines, Diliman.
Keywords: Private schools -- Philippines -- Rizal; School principals -- Philippines -- Rizal; School management and organization -- Philippines -- Rizal